MINERALIZING POTENTIAL DYNAMICS OF CHANGES IN THE ORAL LIQUID IN CHILDREN WITH TYPE 1 DIABETES MELLITUS DURING THE PREVENTIVE MEASURES - Skyba, O.V.; Skyba, V.Ya.; Dienga, A.E.; Babenia, H.O.; Shnaider, S.A.; Savvova, A.O.; Sebov, V.I. (World of Medicine and Biology, 2022)
The research is dedicated to evaluate in children with type 1 diabetes mellitus oral liquid mineral composition in the process of using developed therapeutic and prophylactic complex. Clinical examinations involved 57 children aged 9–12 years, including 45 children with type 1 diabetes mellitus and 12 practically healthy children. At the same time, the condition of the hard tissues of the teeth was assessed. To assess the effect of developed complex on the biochemical parameters of the oral liquid, 45 children with type 1 diabetes mellitus were examined. The use of the proposed complex in children with type 1 diabetes mellitus increased the remineralizing properties of the oral liquid by increasing the content of calcium, phosphorus and magnesium macroelements in it, and also led to an increase in the activity of antioxidant and antimicrobial protection, a decrease in the intensity of lipid peroxidation.
Keywords: dental indicators; biochemical markers; children; metabolic disorder; preventive complex